Surveillance and detection of Mycobacterium tuberculosis complex and Mycobacterium avium complex in captive non-human primates in zoological parks - Lekko, Yusuf Madaki; Ooi, Peck Toung; Omar, Sharina; Mazlan, Mazlina; Sivapalan, Nyanavelan; Ramanoon, Siti Zubaidah; Abdullah Jesse, Faez Firdaus; Jasni, Sabri; Che Amat, Azlan (Faculty Of Veterinary Science, University Of Agriculture, 2022)
Tuberculosis (TB) is a globally important reemerging disease that is chronic, multi host infection caused by Mycobacterium tuberculosis complex (MTBC), which causes disease in livestock, wildlife and zoonotic TB in humans. Twelve (n=12) different species of NHPs were screened for MTBC and MAC in Zoo Melaka, Malaysia. The surveillance of MTBC and MAC was through the application of skin test, serology and PCR. The results showed two orangutan Pongo spp. (16.7%) were reactive to skin test with orangutan A showing obvious swelling of eyelids with drooping and varying degrees of erythema and orangutan B with moderate swelling of the eyelids with drooping and without erythema. For the antibody detection against MTBC, these two orangutans were positive by serology (16.7%), all other NHPs were antibody negative. Polymerase chain reaction from the blood of all NHPs was negative for the MTBC, however, all samples from blood and pharyngeal swab were PCR positive for MAC. In conclusion MAC was detected in captive NHPs population probably due to exposure to the environment without completely discriminating MTBC.